THE COMMUNITY AND ITS RIVALS ACCORDING TO THE "COMMUNITY RULE" FROM CAVES 1 AND 4 - Hempel, Charlotte (Revue de Qumran, 2003)
L'article étudie toutes les références sur les ennemis qui apparaissent dans 1QS // 4QS. Dans les normes communautaires, en commençant par 1QS V, et dans l'Hymne final, le peuple d'injustice et expressions synonymes sont mentionnés souvent dans les moments fondamentaux de l'émergence de la communauté. Les problèmes essentiels entre les membres de la communauté et ce groupe sont la halacha, questions de pureté, échanges économiques, et questions d'autorité. Par contre, dans 1QS I-IV la description des ennemis fait partie d'une vision dualiste du monde, exprimée dans des cadres très différents. This study offers an examination of all the statements about opponents of the community in 1QS // 4QS. In the communal rules beginning with 1QS V as well as the Final Hymn the people of injustice and synonyms are frequently mentioned at defining moments in the community's emergence. Halakhah, purity, economic exchanges and questions of authority emerge as key issues between community members and this group. In 1QS I-IV, on the other hand, descriptions of opponents form part of a wider dualistic worldview expressed in a variety of frames of reference.